DO ENTREPRENEURIAL INTENTION INFLUENCE ENTREPRENEURIAL ATTITUDE? - Martha, Jefry Aulia; Wati, Andy Prasetyo; Indrawati, Aniek; Sulistyowati, Raya; Dirgantari, Puspo Dewi (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This study focuses on determining what factors of entrepreneurial interest can affect student entrepreneurial attitudes, so the population and sample of this study were taken from Business Education Study Program students at the Universitas Negeri Malang, Universitas Negeri Surabaya, Universitas Pendidikan Indonesia, Universitas Negeri Yogyakarta, and Universitas Negeri Jakarta. The sample to be used is 355 respondents with random sampling techniques and online survey applications to collect data from January to April 2023. The analysis technique used is regression analysis. The analysis test results showed that simultaneously, the five independent variables significantly affect the attitude of students in entrepreneurship. In contrast, partially, the variables Locus of Control, Need for Achievement, and Self-Efficacy do not affect students' attitudes toward entrepreneurship, and the variables Risk Taking, and Innovativeness affect the attitude of students toward entrepreneurship. The study results show that the novelty of research emphasizes understanding what factors can bring up the intentions and attitudes of entrepreneurship students. Therefore, there is a need for further research related to variables that can affect student interest in generating a positive attitude towards entrepreneurship.